Analisis kesalahan penggunaan ejaan bahasa indonesia pada karangan narasi peserta didik kelas iv sekolah dasar - Devina Christy Natalia; St Y Slamet; Sukarno Sukarno (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
The research was conducted with the aim of describing the form of errors in the use of Indonesian spelling in the narrative essays of fourth grade students and the factors that cause errors in the use of Indonesian spelling. The method used in this research is descriptive qualitative. The research subjects were fourth grade students and teachers. With Tarigan and Tarigan's language error analysis technique. The forms of errors found include errors in the use of letters by 48.01%, errors in writing words by 35.86%, errors in the use of punctuation marks 13.94%, and errors in writing elements of absorption 2.19%. Factors causing errors in the use of Indonesian spelling, namely from within students, include students' lack of understanding of Indonesian spelling, lack of vocabulary that students understand, and lack of motivation from within students. Then, the causal factors from outside the learners include learning that is not maximized and the influence of the language previously mastered.